SISTEM PERADILAN PIDANA TERPADU (INTEGRETED CRIMINAL JUSTICE SYSTEM) MENURUT KUHAP - Nursyamsudin Nursyamsudin; Samud Samud (Mahkamah : Jurnal Kajian Hukum Islam, 2022)
One of the ideals of the Indonesian people is to implement good governance that reflects democratic values and prioritizes the principle of legal certainty. The creation of a good and integrated law will certainly not be achieved just like that. We need a legal system that can answer and become a tool to achieve the ideals of the nation. Within the criminal justice system, a system known as the Integrated Criminal Justice System is already being implemented. A system in the criminal justice system that becomes a reference for the implementation of a justice that is fair and as expected by the wider community. For synchronization within the criminal justice system itself, it must be synchronized with 3 (three) synchronizations, namely synchronization of substance, structure, and culture. In the criminal justice system, these three pillars must remain in tandem and in sync in order to be able to run a truly integrated criminal justice system.